2012
DOI: 10.4028/www.scientific.net/amr.588-589.968
|View full text |Cite
|
Sign up to set email alerts
|

An <i>In Situ</i> Dissolved Oxygen Monitoring System Based on Fluorescence Quenching Phase Detection

Abstract: As a major indicator in marine life research and geochemistry, the in-situ monitoring of dissolved oxygen has become increasingly important in the assessment of marine ecosystem. It has been proved that fluorescence quenching may result in shorter fluorescence lifetime. Based on it, this paper proposes an in-situ dissolved oxygen monitoring system of high precision and low power consumption applicable to long-term monitoring of complex marine environment. Using phase detecting method, an AC analog amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The sensor had a fast response and was suitable for real-time on-site monitoring. Zhang recommended a phase detection method for the AC analog amplification channel in precision photoelectric detection and adopted the digital phase detection method and the three-order integral average method to detect the phase offset [175]. The experimental results showed that the system has good stability, a high detection accuracy, and a quick response (within 40 s), and it can resist all types of interference.…”
Section: Intelligent Dissolved Oxygen Sensor Technologiesmentioning
confidence: 99%
“…The sensor had a fast response and was suitable for real-time on-site monitoring. Zhang recommended a phase detection method for the AC analog amplification channel in precision photoelectric detection and adopted the digital phase detection method and the three-order integral average method to detect the phase offset [175]. The experimental results showed that the system has good stability, a high detection accuracy, and a quick response (within 40 s), and it can resist all types of interference.…”
Section: Intelligent Dissolved Oxygen Sensor Technologiesmentioning
confidence: 99%